Respuesta :
Answer:
x = -1 and 5
Step-by-step explanation:
Solve: [tex]-16x^2+64x+80=0[/tex]
Factor out common value of 16:
[tex]\implies 16(-x^2+4x+5)=0[/tex]
Divide both sides by 16:
[tex]\implies -x^2+4x+5=0[/tex]
Change signs:
[tex]\implies x^2-4x-5=0[/tex]
Break expression into groups:
[tex]\implies x^2+x-5x-5=0[/tex]
[tex]\implies( x^2+x)-(5x+5)=0[/tex]
Factor parentheses:
[tex]\implies x(x+1)-5(x+1)=0[/tex]
Factor out common term [tex]x+1[/tex]:
[tex]\implies (x+1)(x-5)=0[/tex]
Therefore,
[tex]x+1=0[/tex] and [tex]x-5=0[/tex]
So [tex]x=-1[/tex] and [tex]x=5[/tex]
[tex]\\ \tt\hookrightarrow -16x^2+64x+80=0[/tex]
[tex]\\ \tt\hookrightarrow 16x^2-64x-80=[/tex]
[tex]\\ \tt\hookrightarrow 16(x^2-4x-5)=0[/tex]
- Cancel 16
[tex]\\ \tt\hookrightarrow x^2-4x-5=0[/tex]
[tex]\\ \tt\hookrightarrow x^2-5x+x-5=0[/tex]
[tex]\\ \tt\hookrightarrow x(x-5)+1(x-5)=0[/tex]
[tex]\\ \tt\hookrightarrow (x+1)(x-5)=0[/tex]
- x=-1,5